Analysis of the Need for Teaching Aids in Learning the Concept of Work and Energy to Enhance Students' Understanding - Prihestiyani*, Rini; Dewi, Novi Ratna; Sukaesih, Sri; Listiaji, Prasetyo (Universitas Syiah Kuala, 2025)
The understanding of abstract concepts such as work and energy is often challenging for students at the secondary school level. This study aims to explore the effectiveness of teaching aids in helping students understand these concepts. By using a qualitative case study approach, the research involved observations, interviews, and open-ended questionnaires to gather data from Grade VIII teachers and students at a Madrasah in Grobogan Regency. The findings reveal that teaching aids are instrumental in improving students' understanding of complex concepts like kinetic and potential energy, although their use is constrained by limited resources and budgets. Despite these challenges, students reported greater motivation and comprehension when teaching aids were employed. The study recommends the development of innovative, technology-based teaching aids and further training for teachers in their creation and use. Increased school support and budget allocation are essential to enhance students' learning experiences, particularly in understanding physics concepts such as work and energy